Impacting Capabilities: A Conceptual Framework for the Social Value of Research - Hicks, Daniel J.; Stahmer, Carl; Smith, MacKenzie (Frontiers in Research Metrics and Analytics, 2018)
There is widespread interest in evaluating the social impacts of research and other scholarly activities. Conventional metrics for social impacts focus on economics or wealth creation, such as patents or technology transfer. These kinds of metrics are less appropriate for many scholarly fields, and miss the specific social concerns or needs that researchers aim to address. In this paper, drawing on ideas from ethics and development economics, we develop a conceptual framework for characterizing the social goals of research. We first distinguish resources — such as wealth and intellectual credit — from the goals of scholarship, and further distinguish inward- and outward-facing goals. Outward-facing goals refer to the intended social impacts of research. Next we introduce the Capabilities Approach, a conceptual framework for human well-being developed by ethicists and economists over the last 40 years. This Approach focuses on basic human needs, rather than wealth, and we draw specifically on a list of central human capabilities developed by philosopher Martha Nussbaum. We propose that the items on this list provide a useful starting point for articulating the specific social aims of research. We argue that the Capabilities Approach can facilitate research communication and improve the recognition of public engagement in academic and funding institutions. Familiar bibliographic data and text mining methods can be used in a capabilities-inspired portfolio analysis, and modest changes to existing data collection systems — for tenure and promotion, or research funding applications — could support the development of even richer capabilities-inspired metrics and incentive systems.